2022
DOI: 10.1002/eap.2510
|View full text |Cite|
|
Sign up to set email alerts
|

Both real‐time and long‐term environmental data perform well in predicting shorebird distributions in managed habitat

Abstract: Highly mobile species, such as migratory birds, respond to seasonal and interannual variability in resource availability by moving to better habitats. Despite the recognized importance of resource thresholds, species‐distribution models typically rely on long‐term average habitat conditions, mostly because large‐extent, temporally resolved, environmental data are difficult to obtain. Recent advances in remote sensing make it possible to incorporate more frequent measurements of changing landscapes; however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…Wetlands are typically managed for greater depth to support a broader suite of waterfowl, sometimes to the detriment of shorebirds. Analyses using similar models for shorebirds found that agricultural habitat was more important, especially rice habitat for dunlin (Conlisk, Golet, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wetlands are typically managed for greater depth to support a broader suite of waterfowl, sometimes to the detriment of shorebirds. Analyses using similar models for shorebirds found that agricultural habitat was more important, especially rice habitat for dunlin (Conlisk, Golet, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The 2:1 ratio was based on the average increase in TSS when predicting to the northern region when the North versus South models were used (and when predicting for the south when the South vs. North models were used). Shorebird ensemble models built in this way were superior to models that included the entire study region (Conlisk, Golet, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These predictions can be valuable for assessing habitat suitability or informing the conservation of rare species at locations where occupancy information is uncertain 2 . One approach commonly used in conservation planning is to produce static realizations of species' distributions by pooling spatial data across time, because there may not be enough occurrence data to build models of species' responses to fluctuating conditions 3 . However, ecological processes underlying species' distributions are complex, and averaging temporal variation in habitat suitability or occurrences of highly mobile species may lead to a loss in precision needed for adaptive conservation planning 2,4 .…”
mentioning
confidence: 99%